Electromagnetic Design and Analysis of Inertial Mass Linear Actuator for Active Vibration Isolation System - Do-Kwan Hong; Jang-Hyun Park (Actuators, 2023)
Underwater radiated noise from anthropogenic structures must be reduced to protect the marine environment. Active vibration isolation that can reduce noise generated from vibration sources by providing counteracting forces can solve this issue. This paper presents a 120 N class electromagnetic inertial mass linear actuator for an active vibration control system in a large ship. The proposed actuator is operated based on the Lorentz force, also known as electromagnetic force. To achieve a high thrust force to weight ratio, a permanent magnet with outer radial magnetization is used. In order to design and analyze the proposed model, a simple magnetic equivalent circuit analysis was first conducted to achieve an appropriate force, and its value was compared and verified with the magnetostatic finite element method. The dynamic characteristics of the actuator were then evaluated, and the performance was analyzed at various operating frequency points. The bobbin housing supporting the coil causes an eddy current loss due to materials with electrical conductivity. As a result, the damping force is generated by the reduction in magnetic flux, and the control force tends to decrease.